2009
DOI: 10.1007/s00125-009-1317-8
|View full text |Cite
|
Sign up to set email alerts
|

Islet beta cell failure in the 60% pancreatectomised obese hyperlipidaemic Zucker fatty rat: severe dysfunction with altered glycerolipid metabolism without steatosis or a falling beta cell mass

Abstract: Aims/hypothesis The Zucker fatty (ZF) rat subjected to 60% pancreatectomy (Px) develops moderate diabetes by 3 weeks. We determined whether a progressive fall in beta cell mass and/or beta cell dysfunction contribute to beta cell failure in this type 2 diabetes model. Methods Partial (60%) or sham Px was performed in ZF and Zucker lean (ZL) rats. At 3 weeks post-surgery, beta cell mass and proliferation, proinsulin biosynthesis, pancreatic insulin content, insulin secretion, and islet glucose and lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 48 publications
5
56
0
1
Order By: Relevance
“…We previously studied ZF rats made hyperglycemic by a 60% pancreatectomy and observed subnormal islet expression of PPAR␥ and its target gene GIP receptor versus the hyperexpression in nondiabetic ZF rats (6). The current study has shown the same pattern for PC along with reduced nuclear Pdx1 immunostaining in Px ZF rats, which are in accord with our previous report showing subnormal PC and Pdx1 mRNA expression in Px ZF islets (8).…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellssupporting
confidence: 93%
See 4 more Smart Citations
“…We previously studied ZF rats made hyperglycemic by a 60% pancreatectomy and observed subnormal islet expression of PPAR␥ and its target gene GIP receptor versus the hyperexpression in nondiabetic ZF rats (6). The current study has shown the same pattern for PC along with reduced nuclear Pdx1 immunostaining in Px ZF rats, which are in accord with our previous report showing subnormal PC and Pdx1 mRNA expression in Px ZF islets (8).…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellssupporting
confidence: 93%
“…Collectively, these genes are key controllers of ␤-cell mass, mitochondrial fuel metabolism, and insulin secretion, suggesting the potential for a central role of PPAR␥ in ␤-cell compensation and/or failure. Consistent with this proposal, we have shown increased expression of PPAR␥ and its target genes in islets from rodents with successful ␤-cell adaption to an experimental reduction of ␤-cell mass (4,6) and to obesity and insulin resistance (6,8) and decreased expression in a diabetic rodent model (6,8). Also, clinical trials with thiazolidinedione PPAR␥ agonists (9) have shown a high success rate at stabilizing ␤-cell function and preventing type 2 diabetes (10).…”
Section: Peroxisome Proliferator-activated Receptor ␥ (Ppar␥)supporting
confidence: 75%
See 3 more Smart Citations